Pengaruh Lama Usaha, Jam Kerja, Produk dan Tingkat Pendidikan Terhadap Pendapatan Pedagang Wisata Religi Makam Sunan Kalijaga Kadilangu Demak - Aulia Ulfah (JASIE, 2022)
This study aims to determine and analyze the effect of length of business, working hours, product and level of education on the income of traders. The type of research used in this research is quantitative research. The sample in this study were 50 traders. The type of data obtained in this study is from primary data. Primary data was obtained directly from the main source by filling out a questionnaire directly distributed to traders around the Sunan Kalijaga tomb tourism. The data processing and analysis process uses the data analysis method used in this study is Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of this study indicate that there is a positive effect on the length of business on income and the product has a positive effect on income, while working hours have no effect on income, education level has no effect on income. Keywords: Length of Business, Hours of Work, Product, Level of Education and Income